Evaluation of the effects of tadalafil on pain response in thermal plantar and dynamic plantar tests in rats (Annals of Medical Research, 2021)
Aim: Nitric oxide and its promoters, phosphodiesterase-related agents, have been demonstrated to have pivotal roles in pain modulation. Phosphodiesterase-5 (PDE5) inhibitors are important to enhance the effect of endogenously released nitric oxid. In this study, we aimed to evaluate the tadalafil efficacy, a PDE5 inhibitor, in central nociception models in rats.Material and Methods: Thirty-six rats were divided into six treatment groups. Mechanic plantar aesthesiometer and thermal plantar tests were employed to measure the pain thresholds to the mechanical and thermal stimulations. Correlations between the tadalafil doses, durations and behavioral pain responses were recorded, and compared with that of diclofenac, a nonsteroidal anti-inflammatory drug.Results: Tadalafil 1 and 10 mg/kg single doses; and tadalafil 1 and 10 mg/kg for 7 days exerted significant antinociceptive effects on the mechanic plantar aesthesiometer. However, tadalafildid not reveal significant amelioration in pain responses on the thermal plantar test.Tadalafil 1 mg/kg caused an insignificant amelioration in thermal latencies and withdrawal thresholds in comparison to 10 mg/kg doses.Conclusion: Our findings indicated that nociceptive effect of tadalafil due to thermal stimulation involves cyclic guanosine monophosphate (cGMP), while in mechanic hyperalgesiac GMP may not have a basic role in the primary sensory neurons sensitization. The increase in latencies and withdrawal thresholds with low dose tadalafil was remarkabl.